LYCOPENE CONTENT IN SEVERAL AGES OF TOMATO CALLUS (Lycopersiconesculentum Mill. cv. Rampai) - Yohanes Alvin Goenawan; Katherine Krisyanti Khodjojo; Popy Hartatie Hardjo; Maria Goretti Marianti Purwanto (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2022)
Tomato (Lycopersiconesculentum Mill. cv. Rampai) is rich in lycopene, a carotenoid group compound with many biological activities, one of which is as an antioxidant. Conventional tomato cultivation is not optimal due to the susceptibility of tomato plants to pests and diseases, even though the need for lycopene continues to increase. Plant tissue culture method can be one solution for lycopene production. Callus tomato cv. Rampai was initiated from cotyledons on MS medium (Murashige& Skoog) with the addition of 1 ppm BA (benzyladenine) and 1.5 ppm IAA (indole-3-acetic acid). Callus aged one week to four weeks were harvested and lycopene was extracted by maceration method using hexane:acetone (9:1) as solvent. The presence of lycopene in callus was confirmed by TLC (thin-layer chromatography) (retention factor value/Rf = 0.56) and UV-Vis spectrophotometry (wavelength that gives maximum absorbance = 472 nm). Lycopene content in tomato callus increased with increasing callus age and was directly proportional to the callus growth index. The highest lycopene level was found in callus aged 4 weeks, which was 0.3094 mg/100 g dry weight callus.